A10.13 IGG FC galactosylation changes and predicts response to methotrexate in early rheumatoid arthritis. (24th February 2016) - Hensvold, AH; Lundström, SL; Rutishauser, D; Klareskog, L; Zubarev, RA; Ytterberg, AJ; Catrina, AI
Abstract : Background and objectives: Responses to methotrexate (MTX) treatment for Rheumatoid arthritis (RA) vary across patients, creating the need to find factors that can predict patient response. One potential factor is the ratio between agalactosylated versus galactosylated Fc-glycans. This ratio is known to change according to inflammation- and immune-regulatory disease activities. Material and methods: Using a shotgun proteomics approach, we screened for isotype-specific Fc-glycopeptides directly in serum from 12 healthy individuals and from 59 early RA patients prior to and following three months of MTX treatment. Treatment response was defined according to the European League against rheumatism (EULAR) after three months of treatment. Uni- and multivariate-statistics were employed to interrogate the acquired Fc-glycan data and clinical information. Results: An increase in galactosylated glycans was observed following three months of MTX treatment in patients with moderate and good responses to treatment. Furthermore, MTX non-responders had a significantly lower abundance of galactosylated glycans in blood samples that were collected before treatment compared to the baseline levels of individuals with moderate and good responses to treatment. By using the log10 -ratio between the major agalactosylated and mono- and di-galactosylated Fc-glycans of IgG1, non-responding patients were distinguished from responding patients with 70% sensitivity and 69% specificity. In rheumatoid factor and/or anti-citrullinated peptide-antibody positive patients (n = 44) this sensitivity was increased to 80%. Conclusions: Herein we show that the IgG-Fc-galactosylation status has predictive value for MTX response in early RA, and that it has potential as a predictive factor for use within the clinics.